TILLING. Traditional Mutagenesis Meets Functional Genomics - Henikoff, Steven (American Society of Plant Biologists, 2004)
Most of the genes of an organism are known from sequence, but most of the phenotypes are obscure. Thus, reverse genetics has become an important goal for many biologists. However, reverse-genetic methodologies are not similarly applicable to all organisms. In the general strategy for reverse genetics that we call TILLING (for Targeting Induced Local Lesions in Genomes), traditional chemical mutagenesis is followed by high-throughput screening for point mutations. TILLING promises to be generally applicable. Furthermore, because TILLING does not involve transgenic modifications, it is attractive not only for functional genomics but also for agricultural applications. Here, we present an overview of the status of TILLING methodology, including Ecotilling, which entails detection of natural variation. We describe public TILLING efforts in Arabidopsis and other organisms, including maize (Zea mays) and zebrafish. We conclude that TILLING, a technology developed in plants, is rapidly being adopted in other systems.